Analisis Kebutuhan Bak Penampung Lumpur IPA sebagai Upaya Pengendalian Dampak Lingkungan - Sari, Deasy Ambar; Kamulyan, Budi; Triatmodjo, Bambang (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Sand Drying Bed (SDB) is designed for reducing the potential environmental impact caused by Water Treatment Plants – WTP residuals. Currently, the technical document of SNI (Indonesian National Standard) is still difficult to be applied by the engineer in determining required SDB’s volume based on WTP’s capacity and raw water conditions. The purpose of this research is to analyze WTP’s sludge production for designing SDB’s volume. The research was taken place at Pajangan WTP (50 l/s capacity) and Bantar System of Kartamantul WTP (400 l/s capacity) in Yogyakarta Special Province, which use Progo River as raw water source. The data used in the analysis is raw water turbidity compilation data, TSS (Total Suspended Solid) fluctuations rate of raw water, coagulant dosage used, specific gravity range of dried sludge and imhoff settling ratio based on laboratory tests. The results obtained show that one-year production of dry sludge on Pajangan WTP Unit is estimated to reach 244.55 m3/year from the total number of WTP residual (water and sludge) produced of around 43,158.52 m3/year. Meanwhile, the dry sludge produced on Kartamantul WTP Unit is estimated to reach 1,550.49 m3/year from the total number of WTP residual produced of around 273,635.22 m3/year. Then, each of Pajangan and Kartamantul WTP unit produced about 2.365 m3/day and 1.874 m3/day sludge for every 1 liter/second of raw water. This large amount of sludge leads the SDB has to be better designed.